Association of aortic arch and aortic valve calcifications with cardiovascular risk in patients on maintenance hemodialysis - Liao, Min-Tser; Chao, Chia-Ter; Wu, Chung-Kuan (Frontiers in Cardiovascular Medicine, 2022)
Introduction This study aimed to investigate the association of aortic arch calcification (AoAC) and aortic valve calcification (AVC) with major adverse cardiovascular events (MACE) and cardiovascular and all-cause mortality in patients on maintenance hemodialysis (MHD). Methods This study enrolled 297 adult patients with end-stage kidney disease who were on MHD. They were divided into those with an AoAC score <2 without AVC (n = 70, 23.6%), those with an AoAC score <2 with AVC (n = 96, 32.3%), and those with an AoAC score ≥2 regardless of AVC status (n = 131, 44.1%). We analyzed the risks of MACE, cardiovascular and overall mortality among the three groups using Cox proportional hazard analyses. Survival probabilities were estimated using the log-rank test via the Kaplan–Meier method. Results Kaplan–Meier analysis revealed that the MACE-free rate and the survival rates of cardiovascular and overall mortality were significantly higher in adult chronic hemodialysis patients with AoAC score <2 without AVC, followed by those with AoAC score <2 with AVC, and then those with AoAC score ≥2 (log-rank test; all p < 0.01). The grade of AoAC is a significant risk factor for MACE, cardiovascular mortality, and overall mortality after adjusting for age and gender Relative to AoAC score <2 without AVC, adult chronic hemodialysis patients with AoAC score ≥2 remained an independently significantly risk factor of MACE (adjusted hazard ratio, 2.17; 95% confidence interval 1.11–4.20; p = 0.023) after adjusting for age, sex, and all significant variables in baseline characteristics. Conclusion AoAC grade was positively correlated with a higher risk of MACE and cardiovascular and overall mortality. Furthermore, the presence of AVC modified the adverse cardiovascular risk associated with AoAC in patients on MHD.